Characteristics of Ice Cream with The Addition of Purple Sweet Potato and Porang Flour as A Stabilizer (Faculty of Animal Science Universitas Brawijaya, 2023)
Purple sweet potato and porang are local food ingredients that have potential as stabilizers because they have good hydrocolloid properties. This study was to determine the effect of the addition of porang flour and purple sweet potato with different percentages on ice cream characteristics. This research was prepared using the Complete Randomized Design method in a Nested pattern with 2 factors, first factor (A) is the addition of purple sweet potato(A1) and porang flour (A2), while the second factor (B) is different percentages (0%(B1), 1% (B2), 2% (B3), and 3% (B4)). The parameters observed in this study consisted of overrun, melting time, and emulsion stability (%). The results showed that the addition of purple sweet potato and porang flour with different percentages had a very significant effect (P < 0.01) on overrun and emulsion stability, and a significant effect (P < 0.05) on melting time. The use of purple sweet potato as a stabilizer produced ice cream with better overrun value and melting time compared to ice cream with porang flour stabilizer, but the use of porang flour as a stabilizer produced ice cream with better emulsion stability. The use of purple sweet potato and porang flour with a concentration of 1% produced ice cream with the best characteristics.